Integrating Local Wisdom in Public Services during the Digitalization Era in Indonesia - Jonsa, Alimas; Mardhatillah, Muntaha; Saputra, Ilham Mirza; Aduwina, Aduwina; Ilhamsyah, Fadhil (Universitas Negeri Makassar, 2023)
In the digital era, the integration of local wisdom with public services presents a unique opportunity to enhance community engagement and effectiveness. This study, grounded in qualitative research methodologies, explores how local cultural and traditional knowledge can be seamlessly incorporated into the digital infrastructure of public services. The primary objective is to assess the impact of local wisdom on the efficiency and user satisfaction of public services in a digitized context. By employing in-depth interviews, focus group discussions, and thematic analysis, the research delves into the experiences of community members and service providers. The findings reveal that embedding local wisdom in digital services not only preserves cultural heritage but also increases the accessibility and relevance of these services to the local populace. This approach fosters a sense of community ownership and enhances trust in digital platforms. The study concludes that the marriage of local wisdom with digital innovation in public services not only aligns with contemporary technological advancements but also ensures the retention of cultural identity, offering a balanced path forward in the digitalization era.